A distributed source rate control optimization approach in energy harvesting wireless sensor networks - Wei Wang; Sung Shin (2013 22nd Wireless and Optical Communication Conference, 2013)
In this paper we propose a new distributed scheme to optimize data transmission quality with application level energy neutrality consideration in harvesting wireless sensor networks. The contribution of this proposed scheme is that, the high level data acquisition precision is maximized by properly selecting distributed source coding ancestors. The quality and error robustness tradeoff is adjusted to the ambient harvestable energy in order to improve overall data transmission reliability. We also investigate the effectiveness of applying different power control strategies to different distributed source coding nodes, in order to further improve the overall DSC information gathering quality. Simulation studies demonstrate that the proposed scheme achieves improved data precision with efficient usage of harvestable energy resource.